Rationality is Service Provider’s Trait - Elzbieta SKAPSKA (Communications of International Proceedings, 2020)
Specificity of services requires separate, special treatment as they face the issue associated with rationality. It significantly connects with various factors which are often ascribed only to people. Those factors regard relations and interactions. They constitute a part of organizational potential, but they do not shape any substantive or financial matters. The aim of the article is to explain the notion of rationality and form an attempt to ascribe it to a service provider. Achieving the assigned goal is based on the results of survey research and interviews. Those results concern a cardinal conclusion that rationality, in economic sense and with regard to services, is about conscious acting that brings benefits and, in comparison with production, is far more attached to human reason and market-environment relations. This means that rationality should be a trait of an every economic entity. However, as for a trait of a service provider, it might be understood as a unique skill that a person uses in order to repeat a successful and effective process of service provision based on employer’s involvement in accurate (in accordance with expectations) satisfaction of service consumer needs.
Keywords: Services; Business Activity; Rationality